Redesign of OrthoLPPDUNS External Fixation for Bone Reconstruction Using the Function Analysis System Technique (FAST) Method - Herdiman, Lobes; Priadythama, Ilham; Susmartini, Susy; Priyandari, Yusuf; Murdiyantara, I Nyoman Suci Anindya; Apriani, Durkes Herlina (Jurnal Ilmiah Teknik Industri, 2020)
Taylor Spatial Frame (TSF) better known as an external fixation product from several types of fixation devices in the orthopedic field. The Laboratory of Product Planning and Design has manufactured TSF or called OrthoLPPDUNS external fixations. The OrthoLPPDUNS design found that frame instability forming ring-strut angles caused by strut screw rotations was feeling rough due to backlash. The purpose is how to redesign an OrthoLPPDUNS with a Function Analysis System Technique (FAST). FAST method is applied at each stage of starting from the information stage to the interpretation of the results. The OrthoLPPDUNS design with the joint system uses custom components that cause weakness in frame stability. The use of standard components in joint systems can provide solutions to external fixations, although there are still weaknesses in the ring-strut angle. The OrthoLPPDUNS redesign has a better success rate in terms of stability parameters, allowing more precise bone reconstruction.